Hello, ryguy272!
Then i divided and came up with:
. .
. . . totally stuck
I guess you didn't notice that: . . . so is also a factor.
hey everbody got an assignment from my math teacher today that me and the rest of the class are absolutly stumped on"
f(x) = X^4 - 3x^3 - 13x^2 + 3X + 12
f(-1) = 0
Then i synthetically divided and came up with this unfinished division statement.
Therefore: X^4 - 3x^3 - 13x^2 + 3X + 12
= ( X + 1 ) ( X^3 - 4X^2 - 9X + 12)
= ryguy272 totally stuck
ANY HELP APPRECITATED ( i cant spell )